Strongylus vulgaris : samband med äggurskiljning, ålder och bekämpningsåtgärder - Persson, My (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2019)
Strongylus vulgaris, or large strongyles, is the most dangerous of the equine endoparasites. Its larvae can cause lethal intestinal infarctions when they move through the horse’s blood vessels. Because of its pathogenicity, deworming is recommended when infection is confirmed, regardless of quantity (compare with small strongyles where a small number of worms is tolerated at an individual level). Single deworming of the infected horse may not, however, be enough to eliminate infection entirely. The aim of this study was to explore correlations between occurrences of S. vulgaris and egg per gram faeces, age, number of horses on the farm, and number of months between deworming and faecal sample, respectively. The aim was also to observe 16 S. vulgaris-positive farms during one year to explore which strategy was the most effective in eliminating the parasites, what suggestions horse owners received regarding parasite control, and which advise they chose to follow and why.